(untitled) (Global Scientific Review, 2024)
Another characteristic aspect of a person’s activity in ensuring the stability of society is his ability to interact with a wide range of environments, which plays an important role in communication. The activity of ensuring a culture of communication is of great importance in the competence of a person.